Knowledge, Power, and Justice: A Decolonial Approach to the Epistemic Deconstruction of Education - Sánchez Lara, Ricardo (2022)
This essay proposes a deconstructive approach of structural coordinates that, situated at the intersection of being, knowledge and power, are institutionalized as governmentality devices that organize educational narratives of domination. These narratives are sustained by objectivist and reifying epistemological assumptions articulating hegemonic constructions of knowledge, as a condition for the updating of exclusion systems based on colonial discourses and practices that produce and perpetuate subalternized otherness. Putting the premise of ontological reality in parentheses, we address the relationship between being, knowledge and power as an educational justice issue, focusing on the dimensions of distribution, recognition and participation as axes for the displacement of educational scenarios embedded in colonial frameworks.